Administração crônica de Omeprazol promove alterações comportamentais, inflamatórias e oxidativas no Sistema Nervoso Central de camundongos - Coelho, Dulce Maria Nascimento (2021)
Omeprazole, the first proton pump inhibitors developed, is still widely used in clinical practice and has its widespread use in the population. Despite its great efficacy and considerable safety profile, recently clinical studies have been linking its chronic use to central effects. Currently, the increase in the occurrence of neuropsychiatric disorders is a global concern, and it is essential to identify preventable factors, such as adverse effects to the use of medications. This study aimed at identifying the chronic administration effects of Omeprazole in the CNS of adult mice in a dose equivalent to that used in the clinic, investigating alterations in behavioral, inflammatory and oxidative parameters. For this, C57BL/6 adult male mice, weighing between 20-30g, were used and divided into two groups: OME and Sham, each received either solutions of Omeprazole (8 mg/kg) or vehicle (sodium bicarbonate pH 8.4) respectively, orally by gavage for 28 days. 24 hours after the last administration, the animals were submitted to the following behavioral tests: Open Field (OF) and Rotarod, Forced Swimming Test (FST), elevated plus maze, Y maze (YM), passive avoidance, object recognition (OR) and pre-pulse inhibition. The weight of the animals was registered in 48-72h intervals during the protocol. Moreover, the following brain areas - hippocampus (HP), prefrontal cortex (PFC) and striatum - were dissected, weighted, and the serum was collected. Oxidative stress parameters, malondialdehyde (MDA), nitrite/nitrate and reduced glutathione (GSH), were quantified in brain areas. The inflammatory markers, IL-1β and TNF-α, were measured in peripheral blood and in HP and PFC. The project was approved by the Ethics Committee on the Use of Animals of the Federal University of Ceará filed under no. 1977300718. The following results were observed: a decrease in the crossing parameter in the OF, no change in the motor performance verified by the Rotarod test, a reduction in the immobility time in the FST, an improvement in the percentage of correct alternances in the YM and a reduced in the exploration time in the novel object in the OR. Furthermore, a reduced weight gain and hippocampal weight were observed in Omeprazole-treated mice. Regarding the inflammatory and oxidative stress parameters, there was an increase in the cytokine IL1-β levels in the PFC and serum, whereas TNF-α only in the PFC. Nitrate/nitrite levels increased in HP and PFC, while MDA and GSH levels decreased. These findings suggest that Omeprazole improves depressive-like behavior and working memory, likely through the increase in Nitrate/Nitrite and reduction in MDA levels in PFC and HP. Whereas, the finding regarding the impairment of the recognition memory is more likely to be related to the reduced hippocampal weight. The diminished weight gain might be associated with the IL-1β increased levels in the peripheral blood. Lastly, the results of the present study alongside with the evidence already published, reinforces the cautions and attention concerning the long-term use of Omeprazole should be considered as well as the necessity of doing more studies to better understand the underlying mechanisms behind these effects.